Review on Adjustable Speed Drive Techniques of Matrix Converter Fed Three-Phase Induction Machine - Arsyad Cahya Subrata; Tole Sutikno; Aiman Zakwan Jidin; Auzani Jidin (IAES Indonesia Section, 2018)
Adjustable Speed Drive (ASD) fed Matrix Converter is an interesting topic and is widely discussed in several articles. ASD provides many advantages, especially in the industrial sector because it increases work efficiency so as to reduce production costs. The induction machines construction is sturdy and its relatively inexpensive maintenance makes it more desirable in industrial process applications. Whereas the Matrix Converter (MC) construction without dc-link capacitors makes it more compact compared to conventional converters. This article discussed the ASD control modulation technique by using MC on a three-phase induction motor.